Case Report: Rectus Sheath Hematoma in a Pregnant Women - Alam, Irin Parveen; Yasmin, Fawzia; Jahan, Muna Shalima; Nila, Tahmina Sultana (Bangladesh Journal of Obstetrics & Gynaecology, 2023)
Rectus sheath hematoma is a very uncommon cause of acute abdominal pain, especially during pregnancy. Misdiagnosis is likely due to the lack of specific symptoms, which could put the patient and her fetus in danger.. A patient came with sudden severe left upper abdominal pain with history of cough for few days. She was referred from other hospital and diagnosed there as 32 weeks pregnancy preeclampsia with severe disease with HELLP syndrome. Uterus was tender and more prominent on left side, and patient was not in labour. Provisional diagnosis was abruptio placenta with concealed haemorrhage or rupture uterus. But after laparotomy it was diagnosed as a case of rectus sheath haematoma(RSH). Different imaging modalities such as Ultrasonography and CT are the diagnostic methods. Active bleeding can be managed either surgically by evacuating the haematoma and ligating the bleeding vessels. We managed the patient by laparotomy and blood and blood product transfusion and by multidisciplinary approach, but the patient developed multiorgan failure and expired on 16 th POD. The clinical and diagnostic symptoms of rectus sheath hematoma are highlighted in this case report. Bangladesh J Obstet Gynaecol, 2022; Vol. 37(1): 71-74